1995
DOI: 10.1159/000170214
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin and Cardiovascular Risk

Abstract: We studied the changes in some cardiovascular risk (CVR) factors in 24 maintenance hemodialysis patients treated for 1 year with recombinant human erythropoietin (rHuEPO) either intravenously (12 cases) or subcutaneously (12 cases). In order to clarify whether changes in some parameters were due to direct action of rHuEPO or to changes in food intake, we divided the patients into two groups: group A was formed by 14 patients who showed an increase in their food intake during rHuEPO therapy and group B by 10 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Side effects of chronic EPO administration related to cardiovascular risk factors [14,15] and thrombocytopenia [16] reduce the clinical applicability of EPO as a neuroprotective agent [17]. This has prompted the search for molecules that do not have erythropoietic activity but conserve protective functions.…”
Section: Introductionmentioning
confidence: 99%
“…Side effects of chronic EPO administration related to cardiovascular risk factors [14,15] and thrombocytopenia [16] reduce the clinical applicability of EPO as a neuroprotective agent [17]. This has prompted the search for molecules that do not have erythropoietic activity but conserve protective functions.…”
Section: Introductionmentioning
confidence: 99%
“…If pa tients are not divided into groups according to their acidosis degree, this result cannot be evidenced because of the great variability of Rl values. In a previous investigation [26], in 11 uremic patients selected according to different criteria, we found no significant changes in glucose metabolism param eters after bicarbonate administration.…”
Section: Discussionmentioning
confidence: 58%
“…Indeed, in vitro studies demonstrated that pH and bicarbonate con centration may influence insulin secretion [12][13][14][15][16][17][18] and in sulin binding to receptors [19][20][21][22]. However, in the lit erature, there are few and contrasting reports [23][24][25][26] on effects of metabolic acidosis on glucose metabolism in uremic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the decrease in insulin resistance and, probably, increase in hepatic synthesis of ApoA1 associated with EPO treatment may account for the elevated ApoA1 levels in PD patients. Several studies in the HD population have showed a significant increase in serum ApoA1 concentrations during long-term EPO treatment (4,6,8,10), suggesting that EPO treatment is responsible for this improvement. We have extended this observation to patients undergoing PD, in whom serum ApoA1 concentrations were positively correlated with subcutaneous weekly EPO doses.…”
Section: Discussionmentioning
confidence: 98%